2020
DOI: 10.3892/ol.2020.11795
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KRAS and NRAS mutations on the prognosis of patients with synchronous metastatic colorectal cancer presenting with liver‑only and lung‑only metastases

Abstract: It has been reported that 20-25% of patients with colorectal cancer (CRC) have metastases at the time of diagnosis. Liver and lung are the most common metastatic sites. The aim of the present study was to investigate the association of KRAS and NRAS mutations with clinicopathological features and prognosis of patients with initial liver-metastasis only (LiM-only) or lung-metastasis only (LuM-only) metastatic CRC (mCRC). Overall, 166 patients with CRC with initial LiM-only (n=124) and LuM-only (n=42) were retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Although the mutation in KRAS is an early and dominant event, amplification and overexpression of KRAS, leading to activation of the KRAS/MAPK pathway, can also be observed in colorectal cancer patients [35]. Considering that KRAS mutations have been thoroughly investigated in CRC [36][37][38], we focused our study on patients negative for the most common KRAS activating mutations and showed that wild-type KRAS protein expression could be regulated via miR-544a-3p expression and let-7a-5p KRAS-LCS6 T/G polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mutation in KRAS is an early and dominant event, amplification and overexpression of KRAS, leading to activation of the KRAS/MAPK pathway, can also be observed in colorectal cancer patients [35]. Considering that KRAS mutations have been thoroughly investigated in CRC [36][37][38], we focused our study on patients negative for the most common KRAS activating mutations and showed that wild-type KRAS protein expression could be regulated via miR-544a-3p expression and let-7a-5p KRAS-LCS6 T/G polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…All the primers were produced with standard molecular biology quality (Protech Technology Enterprise Co., Ltd., Taipei, Taiwan). RAS mutations were identified through direct DNA sequencing, the procedure for which was described in detail in our previous study [17]. Both KRAS and NRAS mutation statuses were examined in the patients.…”
Section: Analysis Of Braf Mutation Ras Mutation and Status Of Microsa...mentioning
confidence: 99%
“…In another study, the effect of K-Ras and N-Ras mutation on the prognosis of mCRC specifically in the case of liver-metastasis (LiM) and lung- metastasis (LuM) was assessed. K-Ras as well as N-Ras mutation affected the PFS and the OS of mCRC patients in the case of (LiM) but not in (LuM) [ 187 ]. In a subset of CRC patients who underwent hepatic resection, K-Ras mutations were negatively associated with OS and relapse-free survival (RFS) as well [ 188 ].…”
Section: Future Recommendations For Devising Isoform-specific Targetingmentioning
confidence: 99%